Estimation of the Food Poverty Line - Jose Ramon G. Albert; Wilma Molano (Philippine Institute for Development Studies (PIDS), 2009)
To monitor changes in absolute poverty across time, it is crucial to ensure that the established poverty line is a fixed standard of living that represents the minimum standard required by an individual to fulfill his or her basic food and nonfood needs. Typically, the food (component of the) poverty line is set with the cost of basic needs method, which entails determining the price of some nutritional benchmark through an artifice. In the Philippines, the official food poverty line is estimated at urban and rural areas of each province by using a one-day food menu as the artifice. These menus satisfy energy, and other nutrient requirements. We review the issues raised on this methodology, including the nutritional benchmarks, and propose an alternative approach for estimating the food poverty line using a representative food basket (and some spatial price indices to adjust for differences in cost of living). The proposed methodology addresses issues on consistency raised against the current official approach for setting food poverty lines.
Keywords: 330; absolute poverty line; food poverty line; menu; basket; spatial price index; consistency; Armut; Ernährungssicherung; Grundbedürfnisse; Verbraucherpreisindex; Indexberechnung; Philippinen